Evaluation of obstetric outcomes and prognostic factors in pregnancies with chronic kidney disease - Riza Madazlı; Didem Kaymak; Verda Alpay; Aytac Mahmudova; Nurhan Seyahi (Taylor & Francis Group, 2021)
Objective: To evaluate the obstetric outcomes of pregnancies with chronic kidney disease (CKD) and to assess the prognostic factors on adverse obstetric outcomes. Methods: We retrospectively reviewed 101 singleton pregnancies with CKD. Obstetric outcomes were explored according to CKD stages. The composite adverse obstetric outcome was defined as at least one of stillbirth, neonatal death and delivery <34 weeks due to preeclampsia or fetal distress. Results: The incidences of preeclampsia, fetal growth restriction, perinatal mortality and composite adverse obstetric outcome were 40.5%, 26.7%, 14.8% and 37.6% respectively in pregnancies with CKD. Composite obstetric adverse outcome was significantly higher in pregnancies with CKD stage 4-5 than the other stages (p < 0.01). CKD stage 4-5 and baseline proteinuria >3 g/24 h were associated with composite obstetric adverse outcome (OR 43.2, p = 0.005 and OR 6.08, p = 0.01 respectively) comparing to stage 1 and proteinuria <0.5 g/24 h. Conclusion: Incidences of adverse obstetric outcomes are high even in early stages of CKD. CKD stage 4-5 and baseline proteinuria >3 g/24 h are poor prognostic factors.